Ionic liquid-tethered colloidal silica nanoparticles as a reusable and effective catalyst for the synthesis of phenazines - Hossein Shahbazi-Alavi; Javad Safaei-Ghomi; Mohammad Sadegh Dehghan (Nanochemistry Research, 2020)
Bis (1(3-trimethoxysilylpropyl)-3-methyl-imidazolium) nickel tetrachloride tethered to colloidal nano-silica (ionic liquid/ colloidal nano-silica) has been used as an effective catalyst for the preparation of benzopyranophenazines through the reaction of hydroxynaphthoquinone, o-phenylenediamine, benzaldehydes, and malononitrile under ultrasonic irradiations in ethanol. The catalyst has been characterized by 1H NMR, FE-SEM, EDS, DLS and TGA. Experimental simplicity, excellent yields in short reaction times, wide range of products and applying the sonochemical methodology as an efficient method and innocuous means of activation in synthetic chemistry for the synthesis of medicinally privileged heterocyclic molecules are some of the substantial features of this procedure. The present catalytic method is extensible to a wide diversity of substrates for the preparation of a variety-oriented library of phenazines.